Coat Color Variation and Hair Color Banding in the Papuan Bandicoot (Echymipera kalubu, Marsupialia: Peramelidae) - Maker, Ursula Paulawati; Suryobroto, Bambang; Atmowidi, Tri; Imai, Hiroo; Widayati, Kanthi Arum (Bogor Agricultural University, Indonesia, 2025)
Coat color in mammals plays important adaptive roles, including camouflage, communication, and thermoregulation. Intraspecific variation in coat color is often associated with local environmental conditions. This study investigates coat color and hair color banding in the common spiny bandicoot (Echymipera kalubu), which exhibits ventral color polymorphism. We examined twenty individuals from Manokwari, West Papua, categorizing them into red-ventral and white-ventral groups. Coat color was quantified from digital photographs using CIE Lab* values, and hair color banding types were analyzed microscopically from body areas: dorsal, lateral, and ventral. Significant differences were found between the two groups and among the body areas. Red-ventral individuals exhibited higher a (redness) and b (yellowness) values, especially in the ventral area, whereas white-ventral individuals showed higher L (Lightness) values and reduced chromaticity. Seven hair color banding types were identified, with red-ventral individuals displaying a more diverse hair color banding type across body areas, particularly in lateral and ventral areas. Habitat substrate color analysis revealed that red-ventral individuals inhabited darker, red-yellow environments, whereas white-ventral individuals occupied lighter, less saturated habitats. The dorsal-to-ventral gradient in pigmentation and banding in E. kalubu is predicted to have a countershading function to avoid predators.